PLANT KEY SUCCESS FACTOR THROUGH SPARE PARTS INVENTORY MANAGEMENT - Mohd Sharif, Kamal Imran bin; Ibrahim, Jafni Azhan; Udin, Zulkifli Mohamed; Othman, Abdul Aziz; Hassan, Mohamad Ghozali; Ismail, Mohd Azril; Omar, Mazni; Gilal, Abdul Rehman (International Journal of Supply Chain Management, 2019)
The relationships between a plant operational reliability and its key success factors are discussed in this paper. Several critical factors including effective spare parts management, maintenance approach and continuous improvement is explore along with plant operation reliability. Subsequently, the plant spare parts plays a vital role in many of the global industries and the inventory management of spare parts can be a strategic importance in it as costs and capital are tied together with it in many areas. The key success factors could be applied accordingly for the optimization of the plant that will benefit the stakeholders involved.